Active Processes in the Vocabulary and Word Formation of the Russian Language in the Era of Coronavirus: Linguo-Cognitive Aspect - T. B. Radbil; L. V. Ratsiburskaya; I. V. Paloshi (Научный диалог)
Semantic, lexical and derivational features of the emergence and spread of new phenomena in the speech practice of Russian speakers of the latest period associated with the COVID-19 pandemic are investigated. A linguo-cognitive interpretation of active processes in Russian vocabulary and Russian word formation of the era of coronavirus as formats of knowledge about the changed reality and the new conditions of communication associated with these changes is given. The methods of linguo-cognitive description of the “language of culture” and the method of analyzing active processes at different levels of the language system and methods of its speech implementation are used. The research materials are a dynamic and actively developing Russian-language segment of Internet communication and text data of the Russian National Corpus. Special attention is paid to three groups of new phenomena in the vocabulary of the Russian language associated with the mental and cultural development of the “coronavirus” conceptual space by native speakers: lexical-semantic, lexical and lexical-word-formation innovations. It is shown that active processes of the semantic type find their expression in the phenomena of “new polysemy” and “new homonymy”, as well as non-usual semantic narrowing. It is concluded that new words and expressions not only capture the emergence of new realities of life with coronavirus, but also contribute to the understanding of the changed social reality.